Shared decision-making between patients and healthcare providers at rural health facilities in Eastern Uganda: an exploratory qualitative study - Ranga Solomon Owino; Olivia Kituuka; Paul Kutyabami; Nelson K. Sewankambo (BMC Medical Ethics)
Abstract Background Shared decision-making in healthcare is a collaborative process where patients are supported to make informed decisions according to their preferences. Healthcare decisions affect patients' lives which necessitates patients to participate in decisions concerning their health. This study explored experiences and ethical issues related to shared decision-making in a rural healthcare setting. Methods An exploratory qualitative study was conducted at Budumba Health Centre III and Butaleja Health Centre III in rural Eastern Uganda. In this study, 23 in-depth interviews were conducted among 12 healthcare providers and 11 patients. Data was analyzed thematically using NVivo-12 plus software. Results Four themes emerged which included: Paternalistic cultures of care, challenges, strategies for improvement, and ethical issues. Patients at both facilities expressed the need to be involved in decision-making processes. However, many stressed that they are not engaged in decision-making about their health. Many healthcare providers noted that shared decision-making could improve patient prognosis but are faced with challenges related to low male involvement and the influence of cultural and religious practices, including myths and patriarchal attitudes which impact effective patient engagement. Ethical issues identified include concerns about informed consent, privacy and confidentiality, deception, and harm. Conclusions This study highlighted the need for better sensitization of patients and comprehensive training for healthcare providers to minimize and resolve ethical issues that emerge during shared decision-making processes. Therefore, targeted interventions are needed to enhance decision-making processes in rural healthcare including but not limited to developing shared decision-making manual and continuous training of healthcare providers to ethically engage patients. Further research is needed to explore larger facilities with a bigger scope including patients under 18 years of age and and their surrogates.